2018
DOI: 10.1371/journal.pone.0200445
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of longissimus muscle miRNAomes reveal microRNAs associated with differential regulation of muscle fiber development between Tongcheng and Yorkshire pigs

Abstract: Tongcheng (TC) and Yorkshire (YK) are two pig breeds with distinctive muscle morphology. Porcine microRNAome (miRNAome) of the longissimus muscle during five developmental stages (40, 55, 63, 70, and 90 days post coitum (dpc)) was explored by Solexa sequencing in the present study to find miRNAs involved in the different regulation of skeletal muscle development between the two breeds. A total of 320 known porcine miRNAs, 64 miRNAs corresponding to other mammals, and 224 potentially novel miRNAs were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…This algorithm of Piano is based on the Support Vector Machine (SVM) algorithm and transposon interaction information. The miRNA expression profiles were normalized by transcript per million (TPM), as previously reported [68]. The miRNAs with expression values of >28 TPM in at least one of the 10 libraries were selected for all the following analyses.…”
Section: Prediction Of Novel Mirnas Novel Pirnas and Mirna Target Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…This algorithm of Piano is based on the Support Vector Machine (SVM) algorithm and transposon interaction information. The miRNA expression profiles were normalized by transcript per million (TPM), as previously reported [68]. The miRNAs with expression values of >28 TPM in at least one of the 10 libraries were selected for all the following analyses.…”
Section: Prediction Of Novel Mirnas Novel Pirnas and Mirna Target Genesmentioning
confidence: 99%
“…The expression levels of small RNAs were calculated by using Transcript Per Kilobase Million (TPM) as described in a previous report [69]. Small RNAs with expression value >28 TPM in at least in one of the nine libraries were selected for subsequent data analysis [68]. Raw P-value were convert to adjusted P-value using the Benjamin-Hochberg false discovery rate [70].…”
Section: Differentially Expressed (De) Small Rnasmentioning
confidence: 99%
“…Our preliminary sequencing data showed that miR-543 was differentially and highly expressed in the dorsal longest muscle at different stages during embryonic development, and the expression level was the highest at 70 days of embryo development. 14 Many studies have shown that miR-543 is involved in the regulation of various aspects of tumor cells. [15][16][17] However, less is known about the regulatory role of miR-543 in muscle development.…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of small RNAs were calculated by using Transcript Per Kilobase Million (TPM) as described in a previous report [50]. Small RNAs with expression value >28 TPM in at least in one of the nine libraries were selected for subsequent data analysis [51]. The P-values calculated for every small RNA were adjusted to Q-values for multiple testing corrections by two alternative strategies.…”
Section: Differentially Expressed (De) Small Rnasmentioning
confidence: 99%